Rapid progression of gastric cancer with liver metastasis after discontinuation of lenalidomide in a patient with concurrent multiple myeloma: A case report. (April 2021) - Ujiie, Naoto; Enomoto, Yoshitaka; Takido, Naruhito; Kawaharada, Yasushi; Zuguchi, Masashi; Kubota, Yosuke
Highlights: This is the first report regarding the perioperative management of patients with concurrent multiple myeloma and malignant solid tumor. Our case highlights the need to devise a perioperative management strategy for multiple myeloma patients. Surgeons should be familiar with the risks associated with discontinuation of multiple myeloma drugs. Continuation of the multiple myeloma agent may be preferable in patients who do not have marked myelosuppression. Abstract: Introduction: The synchronous incidence of multiple myeloma (MM) and other primary malignant solid tumor is rare. No detailed studies have been published regarding the perioperative management of patients with concurrent MM and malignant solid tumor. We report a patient with concurrent MM and gastric cancer who experienced rapid progression of liver metastasis after lenalidomide was discontinued. Presentation of case: An 82-year-old woman with MM was diagnosed with clinical T3N2M0 gastric cancer, and MM had been maintained in remission with lenalidomide. Preoperatively, pancytopenia was found, and lenalidomide was discontinued and lenograstim was administered. Blood transfusions were also administered preoperatively due to anemia caused by tumor bleeding. Surgery was performed after her pancytopenia improved. Intraoperatively, several nodules were found on the liver, which were diagnosed as adenocarcinoma metastases. On postoperative day 13, a low density mass in the liver that was not observed before surgery was shown. The patient received best supportive care because she did not desire adjuvant chemotherapy for gastric cancer or resumption of treatment for MM. She died of progressive gastric cancer on postoperative day 80. Discussion: Discontinuation of lenalidomide in our case may have promoted tumor angiogenesis and lowered antitumor immunity, causing rapid tumor growth and liver metastasis. Continuation of the MM agent may be preferable in patients who do not have marked myelosuppression. Conclusion: Surgeons should be familiar with the risks associated with discontinuation of MM drugs when operating on patients with MM and concurrent malignant solid tumor.